COMPLICATIONS AFTER FISTILIZING ANTIGLAUCOMA SURGERY AND METHOD OF TREATMENT (CLINICAL CASE) (World Bulletin of Public Health, 2024)
According to the World Health organization, the number of patients with glaucoma in the world ranges from 60.5 to 105 million people, and in the next 10 years it may increase by another 10 million [1]. The main tasks in the treatment of glaucoma are: reducing and normalizing elevated intraocular pressure, creating conditions for the most favorable microcirculation in the optic nerve, removing the phenomena and consequences of its hypoxia, improving nutrition and tissue metabolism in it [2]. This is achieved through therapeutic and surgical means. The choice of the type of surgical intervention should be determined by the effectiveness and minimum of possible complications. One of the main criteria for making a decision about the operation is the lack of stabilization of the glaucoma process [3, 4]. Surgical treatment of glaucoma is a rather complicated and risky approach, and complications after such operations are not uncommon.